Implementation of STAD Cooperative Learning to Improve Activeness and Learning Outcomes of Class VII B Students at SMPN 22 Semarang (Forum Ilmu Sosial, 2022)
This study is classroom action research, proposing to reveal the possibility of Student Teams -Achievement Division (STAD) to improve the activeness and learning outcomes of Class VII B Students at SMPN 22 Semarang on Social Sciences. It was carried out in two cycles and involved 32 students of Class VIII-B from the second semester of the academic year 2021/2022. Data were collected using observation of students' activeness, as well as posttests of the cycle I and cycle II. The data were analyzed descriptively. The results showed that the average percentage of student activity increased from 56.72% pre-cycle to 67.66% in cycle I and to 78.28% in cycle II. Student learning outcomes also experienced an increase in pre-cycle average scores from 71.56 to 76.25 in cycle I and 85.88 in cycle II. Students who completed the study were 13 students (40.63%) in the pre-cycle, 22 students (68.75%) in cycle I, and 30 students (93.75%) in cycle II. Based on the research results, the STAD model can improve learning outcomes and the activity of class VIII-B students of SMPN 22 Semarang through cooperative learning.